Enhanced efficacy of transforming growth factor-β1 loaded an injectable cross-linked thiolated chitosan and carboxymethyl cellulose-based hydrogels for cartilage tissue engineering. Issue 18 (12th December 2021) - Zhang, Zefeng; Lin, Shufeng; Yan, Yipeng; You, Xiaoxuan; Ye, Hui
Abstract: Growth factors (GFs) are soluble proteins extracellular that control a wide range of cellular processes as well as tissue regeneration. While transforming growth factor beta-1 (TGF-β1) promotes chondrogenesis, its medical use is restricted by its potential protein instability, which necessitates high doses of the protein, which can result in adverse side effects such as inefficient cartilage formation. In this work, we have developed a novel hydrogel composite based on the polymer, cross-linked thiolated chitosan; TCS and carboxymethyl cellulose; CMC (TCS/CMC) hydrogel system was utilized as injectable TGF-β1 carriers for cartilage tissue engineering applications. Rheological measurements showed that the elastic modulus of TCS/CMC hydrogels with an optimized CMC concentration could reach around 2.5 kPa or higher than their respective viscous modulus, indicating that they behaved like strong hydrogels. Crosslinking significantly alters the overall network distribution, surface morphology, pore size, porosity, gelation time, swelling ratio, water content, and in vitro degradation of the TCS/CMC hydrogels. TCS/CMC hydrogels maintain more than 90% of their weight and retain their original form after 21 days. TGF-β1 released marginally from TCS/CMC hydrogels as incubation time increased, up to 21 days, with around 18.6 ± 0.9% of the drug stored inside the TCS/CMC hydrogels. On day 21, BMSC treated with TGF-β1 in medium or TGF-β1-loaded TCS/CMC hydrogels grew faster than the other groups. For in vivo cartilage repair, full-thickness cartilage defects were induced on rat knees for 8 weeks. The optimal ability of this novel TGF-β1-loaded TCS/CMC hydrogel system was further demonstrated by histological analysis, resulting in a novel therapeutic strategy for repairing articular cartilage defects. GRAPHICAL ABSTRACT: UF0001 Research Highlights: An in situ forming and injectable thiolated chitosan and carboxymethyl cellulose hydrogel was fabricated for cartilage tissue engineering. TCS/CMC displays suitable gelation time with high swelling ratio, tunable mechanical properties and highly porous. TGF-β1-loaded-TCS/CMC hydrogels showed maximum drug release activity. TGF-β1-loaded-TCS/CMC hydrogels had good biocompatibility to articular chondrocytes. An injectable TCS/CMC/TGF-β1 hydrogel is a promising material system for cartilage tissue engineering.